Effect of Gestalt therapy on assertiveness of nursing students. - Maryam Moghimian; Razieh Amini; Fahimeh Kashani (Guilan University of Medical Sciences, 2016)
Introduction: Assertiveness, is one of the life skills that effects on increasing self-esteem, logical expression of thoughts and feelings, reducing anxiety, improving social communication skills and supporting human rights and finally increasing life satisfaction and happiness Objective: This study aimed to determine effects of Gestalt therapy on assertiveness of nursing students Methods: The pilot of study is situated on clinical trial research experiment, from side to side pre and post control group. Among 80 nursing students enrolled in Nursing and Midwifery school of Islamic Azad University Najaf Abad in 2013-2014 who trained in the field, all those who could not expressed themselves were 36 subjects which measured with ASA scale and 24 subjects who want to enter to the research were separated randomly into experimental and control group. Experimental group consisting of Gestalt therapy, two-hours per session for 8 sessions, were trained. The control group did not receive the interventions. Therefore data analysis performed compairing the mean scores, paired t- test and Independent T Test Results:In experimental group, the mean scores of assertiveness after intervention increased significantly (P<0/001). The mean scores of assertiveness of the control group showed no increase significantly (p=0/4). Comparison between mean score of assertiveness after and before of intervention in experimental group with control group was significant (p<0/005). Conclusion: Gestalt therapy is effective on increasing of assertiveness. Thus, according to the results of this research, the methods of psychotherapy could be useful and might select, to reduce beliefs and ineffective components